A new species of Onthophagus (Scarabaeoidea: Scarabaeinae) from the Mexican Transition Zone, with remarks on its relationships and distribution - Arriaga-Jiménez, A.; Moctezuma, V.; Rossini, M.; Zunino, M.; Halffter, G. (Zootaxa, 2016)
A new American Onthophagus of the chevrolati species-group is described (Onthophagus bolivari sp. nov.), providing also identification keys to the aztecus complex. Dorsal habitus and genital structures of the new species are illustrated. The relationships and geographical distribution of the aztecus complex are discussed, giving particular attention to the evolutionary history of O. bolivari.